The stress induced phase transformation in martensitic single crystal of Cu-Zn-Al alloys. - Barceló, G. N.; Ahlers, Manfred Hermann; Rapacioli, R. (Deutsche Gesellschaft für Metallkunde, 1979)
Fil: Barceló, G. N. Comisión Nacional de Energía Atómica; Argentina